Assessing the vulnerability and risk of maize to drought in China based on the AquaCrop model. (April 2021) - Zhu, Xiufang; Xu, Kun; Liu, Ying; Guo, Rui; Chen, Lingyi
Abstract: In the context of global climate change, droughts pose a serious threat to agricultural development and food security. Assessing the vulnerability and risk of regions to drought is important for its prevention. In this paper, to understand the vulnerability of maize to drought in different regions of China and quantify its risk, 241 prefecture-level administrative regions (including prefecture-level cities, autonomous prefectures, prefectures, and leagues) in the five main maize-growing regions of China are used as study area. By using a method of global sensitivity analysis, the extended Fourier amplitude sensitivity test (EFAST), we chose two parameters that are most sensitive to maize yield to calibrate the AquaCrop model. We then used it to simulate the water stress of maize in the study area under different irrigation scenarios as well as the corresponding production. We defined the drought hazard index (DHI) as the daily average of the crop water stress indicator during the growing season, and used it to describe the intensity of droughts. Vulnerability curves (the function of the DHI and rate of yield loss) of the entire growth season and various stages of growth were also formulated. These were used to determine the loss of maize yield under four levels of risk (return periods of 5, 10, 20, and 50 years). The results showed the following: 1) the vulnerability curve of maize for the entire growing season was consistent with logistic function, and the coefficient of determination of the equation of regression was R 2 = 0.93. The rate of yield loss began increasing rapidly once the DHI had reached 0.2 and approached its maximum value when the DHI was 0.6. 2) The coefficients of determination of the results of regression in 14 scenarios, in which drought had occurred in different stages of growth, were between 0.28 and 0.92. Drought from the tasseling stage to the milk stage had the most significant negative effect on the maize yield, followed by the seventh leaf stage to the tasseling stage and the sowing stage to the seventh leaf stage. Drought from the milk stage to physiological maturity had the least negative effect on the maize yield. 3) Under all four risk levels, the DHI and the yield loss rate of maize in China decreased from the northwest to the southeast. The Northwest Irrigated Maize Region had the highest drought risk among the five maize-growing regions, followed by the North Spring Maize Region, the Huang-Huai-Hai Summer Maize Region, the South Hilly Maize Region, and the Southwest Mountain Maize Region. 4) The DHI calculated by the average method was more representative than that calculated using the accumulative method. Graphical abstract: Unlabelled Image Highlights: A new drought hazard index was proposed for building drought loss curves. Drought vulnerability curves were built for five main maize-growing regions in China. Yield loss curves of maize were built for droughts occurred in various growth stages. Risk of maize yield loss for return periods of 5, 10, 20, and 50 years were assessed. The drought risk of maize in China decreases from northwest to southeast.